In vitro evaluation of aflatoxin m1 control potential of six essential oils in Benin - SESSOU, PHILIPPE; FAROUGOU, SOUAÏBOU; TCHOBO, PAUL FIDÈLE; AGBANGNAN, P.; ADJALIAN, HENRI; AZOKPOTA, PAULIN; YOUSSAO ABDOU KARIM, ISSAKA (My University, 2013)
Aflatoxin M1 (AFM1) is hepatocarcinogen frequently found in cheese. Its presence in this foodstuff constitutes a serious threat for consumers. The present study had evaluated aflatoxin M1 control potential of six essential oils against synthetic aflatoxin M1. It had consisted to blend Aflatoxin M1 diluted in acetonitrile (1μg/mL) with essential oil to achieve final concentrations of 2%, 4%, 6%, 8% and 10% of oil and to follow the disintegration of this AFM1 in the meantime of 30 minutes, 1, 2, 3, 4, 5 and 24 hours on silica gel with or without thin layer chromatography assay (TLC). The results obtained revealed that at the concentrations tested, no fluorescence was observed for the mixtures of Aflatoxin M1 with C. zeylanicum, P. racemosa and Syzygium aromaticum essential oils on silica gel without chromatography assay contrary to results obtained for the same mixtures after chromatography assay. The mixture of Cymbopogon citratus showed fluorescence with or without TLC assay. Pure extracts of Ocimum gratissimum and Zingiber officinale showed a green fluorescence. In sum, all the essential oils tested didn’t possess capacity to destroy AFM1 at concentrations investigated. Although, these extracts cannot be used for controlling aflatoxin M1, their potentiality for inhibiting mycotoxins production by moulds can be considered.
Keywords: Aflatoxin M1; antiaflatoxin assay; essential oils; TLC assay